Odontogenic maxillary sinusitis and oroantral communication: A case report - Dipankara, Jackson; Hadrian, Gary; Eddy; Putri, Tansza Setiana; Rinanti, Astri; Swe, Thet Thet; Poedjiastoeti, Wiwiek (Dental Journal (Majalah Kedokteran Gigi), 2025)
Background: Odontogenic maxillary sinusitis (OMS) and oroantral communication (OAC) have been well recognized in oral and maxillofacial surgery. The treatment ranges from non-surgical treatment to surgical treatment. Purpose: This case report discusses the management of OMS and OAC through a non-surgical approach. Case: A female patient presented to our department after being referred from a different department. After informed consent was obtained, her tooth was extracted. Unfortunately, the maxillary sinus was exposed, and OMS was suspected after pus leakage occurred into the oral cavity prior to tooth extraction. The communication was found at the mesiobuccal region with a 3 mm diameter and distobuccal region with a 2 mm diameter. Case management: Due to the small size of the OAC, it was decided to close the communication using the figure-of-eight suture technique, and an absorbable gelatin sponge was placed inside the socket. Odontogenic maxillary sinusitis was treated with a combination of pharmacological therapy and dental therapy, including the removal of the source of infection and a prescription of antibiotics and nasal decongestant due to the OAC. Finally, the patient was educated about the sinus precaution step. Conclusion: Good healing of the lesion was noted in this report. Non-surgical treatment such as dental therapy and pharmacological therapy can, therefore, be considered to treat OMS. Closure of the OAC using a suture technique and a gelatin sponge can treat small-sized communication.